Evaluating digital corporate identity: Application of AHP method in website quality analysis - Marinović, Nevena; Vlastelica, Tamara; Krstić, Jelena (Industrija, 2023)
Due to the increasing importance of websites as elements of digital corporate identity, website quality has become an area of great importance in practice and academic research. The goal of the research is to evaluate the quality dimensions of the website and determine their importance in choosing the most desirable option among several competing options. Given that the online visibility of companies from the construction industry is unsatisfactory, this sector was selected for the research, and the web pages of selected companies from this sector were analyzed. By using the Analytical Hierarchy Process (AHP) method, it was examined which dimensions of quality have the greatest influence on the quality of a web page. It was found that loading speed (0.703) and information quality (0.554) have the greatest influence on the quality of the website. The results of the research can be used by companies and web designers in practice, in order to make the proper decisions regarding website content, design and functionality and their use in the context of improving the digital corporate identity.
Keywords: website quality, quality dimensions, digital corporate identity, AHP